Cultural Antecedents to Community: An Evaluation of Community Experience in the United States, Thailand, and Vietnam. (June 2018) - Muir, Jonathan A.; Braudt, David B.; Swindle, Jeffrey; Flaherty, Jeremy; Brown, Ralph B.
To what extent does community experience differ between low–context and high–context societies? Prior literature theorizes that community experience consists of two separate, yet highly related concepts: community attachment, an individual's general rootedness to a place, and community satisfaction, how well an individual's community meets their societal needs. We test this conceptualization of community experience across communities in the United States and two Southeast Asian nations: Thailand and Vietnam. We argue that Southeast Asian nations constitute "high–context" societies with relatively high social integration and solidarity while the United States is more individualized and less socially integrated and thus constitutes a "low–context" society. Our results provide empirical evidence that individuals' experience of community varies between low– and high–context societies. These results demonstrate that cultural context continues to matter in regards to the lived experience of community and researchers need to remain vigilant in accounting for such differences as they seek to examine the concept of community more broadly.